Det sårbare selv i rampelyset: Adaptationen af den sårbare forfatter som kildetekst hos Elias Sadaq og Glenn Bech - Holde, Asger (Passage - Tidsskrift for litteratur og kritik, 2025)
Desire and Resistance: Katie Mitchell’s Staging of Miss Julie and Alphabet This article explores Katie Mitchell’s 2010 staging of Miss Julie at Schaubühne, where she employs live cinema and integrates Inger Christensen’s Alphabet to deconstruct Strindberg’s patriarchal structures. By shifting the focus to Kristine, Mitchell creates a feminist counter-narrative, merging naturalism with postdramatic techniques. The analysis highlights how Mitchell’s hybrid form challenges traditional hierarchies of text and stage, offering a critical dialogue between theatre, literature, and film.